Analysis Of Islamic Educational Values In The Implementation Of The Project Of Strengthening Pancasila Student Profile Theme Of Local Wisdom At SMKN 1 Purwosari - Fatimah Sampini; Ahmad Marzuki; Ali Mohtarom (Sean Institute, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that participants actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character and the skills needed by themselves and society. In order to prepare qualified human resources who are ready to compete in the digital era, education needs to adapt the curriculum use. The project to strengthen Pancasila student profiles is a cross-disciplinary learning in observing and thinking about solutions to problems in the surrounding environment to strengthen various competencies in the Pancasila student profile. with the change in the curriculum, it certainly changes a lot of educational structures, therefore, there is still not much data written regarding the implementation of a project to strengthen the profile of Pancasila students in an institution that has implemented an independent curriculum. In all activities that have been implemented in the chosen project theme, there is also a secret meaning to the value of Islam's education. This research aims at finding out how the project is being used to enhance the profile of Pancasila student with the theme of local wisdom, and at finding out the values of Islamic education that exist in the activities of the project, in order to strengthen the profile of Pancasila students with the theme of local wisdom. It is a qualitative approach used by researchers. Observation, interviewing, and documentation shall be methods of application. the values of Islamic education include the values of faith, morals and worship in activities, according to the result of the research carried out in the field of local wisdom activities, which include the implementation of the profile of Pancasila student project in five strages; Intrduction, contextualization, real action, reflextion and follow up activities. Those values are gratitude to Allah SWT for his mercy and favors, mutual cooperation and responsibility, and devotion to ritual worship as evidence of human obedience to his commands.